IMPLEMENTASI RPG MAKER MV PADA GAME RPG TOWER OF ETERNITY - Muhammad Fauzhan Nasril; Yuli Maharetta Arianti; Nani Mintarsih (Jurnal Teknik dan Science, 2023)
The development of technology has brought about changes in various aspects of human life, one of which is the entertainment media, namely video games. Video games are a common form of entertainment that typically follows certain rules, providing opportunities for achieving victory. Video games encompass various genres, one of which is RPG (Role-Playing Game), which usually emphasizes gameplay, story, and characters. The game "Tower of Eternity" was created using RPG Maker MV software version 1.6.2. The method used in the game's development is SDLC (System Development Life Cycle). The purpose of creating this game is for entertainment and to foster an interest in playing RPG genre games. The game has undergone testing in two stages: Functional testing and Device testing. Functional testing revealed that most of the buttons can be used effectively. Device testing on 5 devices, including a PC, Asus N551ZU laptop, Asus Vivobook X513EAN laptop, Asus VivoBook X421EAY laptop, and Toshiba Protege Z830 laptop, showed that 3 devices ran very well, 1 device ran reasonably well, and 1 device ran less efficiently. The required device specifications to run this game are AMD FX 7600P, 8GB RAM, and Radeon R9 M280x 4GB GDDR5.